2020
DOI: 10.1017/s000711452000255x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma mineral (selenium, zinc or copper) concentrations in the general pregnant population, adjusted for supplement intake, in relation to thyroid function

Abstract: The current study reports on first-trimester reference ranges of plasma mineral Se/Zn/Cu concentration in relation to free thyroxine (FT4), thyrotropin (TSH) and thyroid peroxidase antibodies (TPO-Ab), assessed at 12 weeks’ gestation in 2041 pregnant women, including 544 women not taking supplements containing Se/Zn/Cu. The reference range (2.5th – 97.5th percentiles) in these 544 women was 0.72 – 1.25 µmol/L for Se, 17.15 – 35.98 µmol/L for Cu, and 9.57 – 16.41 µmol/L for Zn. These women had significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
3
16
1
Order By: Relevance
“…Similarly, one of the main findings in this cohort is that women with low plasma selenium concentration were more likely to have abnormal TSH concentrations (predominately < 0.4 mIU/L). A similar result was also reported in an observational study of pregnant Netherlands (n = 2041) at 12‐week gestation, 33 and the authors suggested human gonadotropin hormone may interfere with the role selenium plays in synthesising thyroid hormones. In contrast, a secondary analysis of the effects of antenatal selenium (60 µg/day) supplementation among UK pregnant women (n = 114) living in an area of mild‐to‐moderate iodine‐deficient area reported decreased TSH in the selenium supplementation group.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, one of the main findings in this cohort is that women with low plasma selenium concentration were more likely to have abnormal TSH concentrations (predominately < 0.4 mIU/L). A similar result was also reported in an observational study of pregnant Netherlands (n = 2041) at 12‐week gestation, 33 and the authors suggested human gonadotropin hormone may interfere with the role selenium plays in synthesising thyroid hormones. In contrast, a secondary analysis of the effects of antenatal selenium (60 µg/day) supplementation among UK pregnant women (n = 114) living in an area of mild‐to‐moderate iodine‐deficient area reported decreased TSH in the selenium supplementation group.…”
Section: Discussionsupporting
confidence: 83%
“…Besides, in sample selection, time of day, food and the consumed meals' interval, recent exercise, or other forms of stress all can result in obvious fluctuations [17]. In our study, serum zinc concentration was obviously higher than the value reported in previous Chinese studies [18], similar to the data in some countries and regional documents, but slightly lower than the results of USA [19], EU [20,21], Korea [22], and Japan [23]. In this regard, there was a trivial difference in zinc deficiency prevalence as compared to the significant changes in serum zinc concentration.…”
Section: Discussionsupporting
confidence: 80%
“…The baseline characteristics of both groups are shown in Table 1. Hashimoto's disease was diagnosed based on value >35 U/L for anti-thyroid peroxidase (anti-TPO) antibodies and >20 U/L for thyroglobulin (anti-TG) antibodies [23,24]. In the group of women with Hashimoto's disease, 45.2% managed to balance the level of hormones regulating thyroid function.…”
Section: Study Populationmentioning
confidence: 99%